Les informations policières à Paris entre 1667 et 1830. Production, usages et pratiques de gouvernement - Nicolas Vidoni (Amnis)
In order to be efficient when acting in town, the Police, between 1667 and 1830, made information about persons and material space, especially in Paris. This information was used in the governmental decision process, and modified the police practices themselves. Therefore, this « dialectic » between urban space and administrative and political spheres can be analyzed in terms of police information.